PEMAHAMAN CADAR, HIJAB, DAN BURQA DALAM PERSPEKTIF ISLAM - Muhammad Syihab Al Faruqi; Maulana Muzayyin Al Kahf; Maulida Fitria Rahmah (STAI Asy-Syukriyyah, 2023)
Some people think that Islam is a religion that originated from the Arabs. This statement arises because Islam requires all Muslim women to always cover their genitals and wear the headscarf. This is because the clothing that is obligatory for Muslim women contains elements of the culture of the Arabian peninsula. In fact, these clothes have been around since the ancient Persians who were included in the clothing of choice. This is caused by an understanding that is not in accordance with the history of civilization about the hijab from time to time. Through this research explores Islamic sources, such as the Qur’an, Hadith, and related interpretations, to understand the legal basis and traditional understanding of the headscarf, veil, and burqa. By using qualitative methods and a narrative study approach that includes recordings of life history, as well as researching issues that are basically general, then gets a focus on things that are more specific. This scientific writing aims to research about promoting culture, the issue which states that Islam has changed the customs that exist in Indonesia, and the laws of the veil, headscarf and burqa. So that in this research it has been found about the history of the development of the veil, headscarf, and burqa, as well as the law. The use of the headscarf is basically just to cover the nakedness and protect them from social evils.